Extending Kubernetes : making use of work queues, reconciliation loops, controllers, and operators - Arbezzano, Gianluca (O'Reilly Media, 2019)
Kubernetes use has grown quickly--not simply for convenience or efficiency but for its extensibility and capacity to adapt to any environment. If you're a software engineer with a working knowledge of Kubernetes, this practical report demonstrates how to extend this container orchestration system to take advantage of all its capabilities. Specifically, you'll learn how to use work queues, reconciliation loops, controllers, and operators. Gianluca Arbezzano from InfluxData shows you why Kubernetes is much more than an end application. Extending Kubernetes with its API to implement and automate flows or to gain more visibility into your system more than justifies the system's cost and complexity. With this report, you'll learn the right way to use everything it has to offer. Make Kubernetes a commodity to achieve stability, security, and a simpler UX Learn why Kubernetes extensibility can help you provide a solid user experience Explore the Kubernetes API and its software development kits, including the Go SDK Create easy but powerful integration using the CRUD client or kubectl plug-ins Explore Kubernetes primitives, including shared informers, the work queue, and custom resource definitions.